2017
DOI: 10.1007/s11356-017-8566-8
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater treatment and public health in Nunavut: a microbial risk assessment framework for the Canadian Arctic

Abstract: Wastewater management in Canadian Arctic communities is influenced by several geographical factors including climate, remoteness, population size, and local food-harvesting practices. Most communities use trucked collection services and basic treatment systems, which are capable of only low-level pathogen removal. These systems are typically reliant solely on natural environmental processes for treatment and make use of existing lagoons, wetlands, and bays. They are operated in a manner such that partially tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 68 publications
(90 reference statements)
0
19
0
Order By: Relevance
“…The presence of pathogens in the effluent may pose a risk to human health through various exposure pathways but this will obviously depend on the number and survival of the pathogens being released into the arctic environment and the human and wild-life interactions with 553 impacted areas (Harper et al 2011, Daley et al 2017. The predicted infectious dose for pathogenic enterohemorrhagic E. coli serotypes such as O157:H7 is only 10 to 100 bacteria 555 (Theron and Cloete 2002), while for L. monocytogenes it is 10 7 -10 8 CFU in healthy hosts and 556 10 5 -10 7 CFU in susceptible individuals (Farber et al 1996).…”
Section: Wsp Temperature and Removal Of Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of pathogens in the effluent may pose a risk to human health through various exposure pathways but this will obviously depend on the number and survival of the pathogens being released into the arctic environment and the human and wild-life interactions with 553 impacted areas (Harper et al 2011, Daley et al 2017. The predicted infectious dose for pathogenic enterohemorrhagic E. coli serotypes such as O157:H7 is only 10 to 100 bacteria 555 (Theron and Cloete 2002), while for L. monocytogenes it is 10 7 -10 8 CFU in healthy hosts and 556 10 5 -10 7 CFU in susceptible individuals (Farber et al 1996).…”
Section: Wsp Temperature and Removal Of Pathogensmentioning
confidence: 99%
“…People living in Nunavut communities may particularly be at risk as their diets are reliant on the local harvest of food from traditional sources (Daley et al 2014). In addition, recreational activities often take place near wastewater effluent discharging areas (Harper et al 2011, Daley et al 2017. Finally, the overcrowded housing in these communities may be exacerbating the frequency of inter-person spread of infectious agents (Goldfarb et al 2013, Harper et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…The issue of antibiotic resistance is of particular importance in the Canadian Territory of Nunavut, which is primarily inhabited by Inuit who practice a number of food harvesting activities (hunting, fishing, shellfish harvesting, etc.) that may create exposure pathways with wastewater constituents including ARBs (Daley et al, 2015(Daley et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature of water in the septic tank was 2-4 degrees Celsius in the cold season. This is one of the main reasons for unsatisfactory biological wastewater treatment [2,6,8,9,32].…”
Section: Preliminary Study Of the Initial Wastewater Temperature And mentioning
confidence: 99%
“…The tendency of unsatisfactory performance of biological treatment can be found not only in the territory of the Russian Federation but also in the territory of foreign countries, such as Greenland [5], the Canadian Arctic [6,7], the state of Alaska (USA) [8], Northern Norway, Finland, and others. Research revealed that the concentration of pollutants in the conditions of a decentralized wastewater disposal system was two to three times higher in the obtained water compared with in samples from a centralized sewage in other regions [9].…”
Section: Introductionmentioning
confidence: 99%